Expression and mechanisms of interferon-stimulated genes in viral infection of the central nervous system (CNS) and neurological diseases - Lang, Rui; Li, Huiting; Luo, Xiaoqin; Liu, Cencen; Zhang, Yiwen; Guo, ShunYu; Xu, Jingyi; Bao, Changshun; Dong, Wei; Yu, Yang (Frontiers in Immunology, 2022)
Interferons (IFNs) bind to cell surface receptors and activate the expression of interferon-stimulated genes (ISGs) through intracellular signaling cascades. ISGs and their expression products have various biological functions, such as antiviral and immunomodulatory effects, and are essential effector molecules for IFN function. ISGs limit the invasion and replication of the virus in a cell-specific and region-specific manner in the central nervous system (CNS). In addition to participating in natural immunity against viral infections, studies have shown that ISGs are essential in the pathogenesis of CNS disorders such as neuroinflammation, and neurodegenerative diseases. The aim of this review is to present a macroscopic overview of the characteristics of ISGs that restrict viral neural invasion and the expression of the ISGs underlying viral infection of CNS cells. Further, we elucidate the characteristics of ISG expression in neurological inflammation and neuropsychiatric disorders such as depression as well as neurodegenerative disorders including Alzheimer's disease (AD), Parkinson's disease (PD) and amyotrophic lateral sclerosis (ALS). Finally, we summarize in detail the roles of several ISGs (ISG15, IFIT2, IFITM3) that have been studied more in recent years in CNS antiviral as well as disease and its mechanisms, providing an important target for the development of novel antiviral drugs and anti-neurological disease drugs.